THE CHARACTER VALUE IN THE FAIRY TALE "CERITA CALON ARANG" BY PRAMOEDYA ANANTA TOER AS A MEANS OF EARLY CHILDHOOD EDUCATION - Afandi, Iswan (Jurnal Pendidikan Karakter, 2020)
The purpose of this study is to describe the value of characters found in fairy tales. This type of research is descriptive qualitative research with content analysis techniques. The theory used is the theory of children's literature and character education. Source of research data in the form of a fairy tale entitled The Story of Candidate Charcoal by Pramoedya Ananta Toer totaling 100 pages published by PT. Lantern Dipantara in 2003. Data validity was tested using data triangulation and method triangulation. Data analysis is carried out in stages: a) identification of fairy tales as research objects; b) data reduction; c) data presentation; d) interpretation of data according to children's literary theory and character education; e) inference (Miles & Huberman, 1994). The results of the study found fourteen character values, namely: wise, socially caring, fond of reading, prominence, compassion, democratic, good decision-makers, good citizens, care for the environment, religious, respectful, cooperation, curiosity, and brave character. This research shows that fairy tales can be used as teaching materials for character education. However, development research needs to be done regarding increasing crime in the community. Various efforts in transmitting the values of character education to students have been carried out both in the family, school, and community environment.